Artifact Correction in Temperature-Dependent Attenuated Total Reflection Infrared (ATR-IR) Spectra. Issue 8 (August 2017) - Sobieski, Brian; Chase, Bruce; Noda, Isao; Rabolt, John
A spectral processing method was developed and tested for analyzing temperature-dependent attenuated total reflection infrared (ATR-IR) spectra of aliphatic polyesters. Spectra of a bio-based, biodegradable polymer, 3.9 mol% 3HHx poly[(R)-3-hydroxybutyrate- co -(R)-3-hydroxyhexanoate] (PHBHx), were analyzed and corrected prior to analysis using two-dimensional correlation spectroscopy (2D-COS). Removal of the temperature variation of diamond absorbance, correction of the baseline, ATR correction, and appropriate normalization were key to generating more reliable data. Both the processing steps and order were important. A comparison to differential scanning calorimetry (DSC) analysis indicated that the normalization method should be chosen with caution to avoid unintentional trends and distortions of the crystalline sensitive bands.